SURGICAL MENOPAUSE IN WOMEN OF REPRODUCTIVE AGE - V. A. Kulavskii; E. V. Kulavskii; A. M. Ziganshin (Акушерство, гинекология и репродукция)
The article represents peculiarities of the origination and treatment of surgical menopause at women of reproductive age, principles of monitoring and approaches to the hormonal therapy. In spite of the high efficiency of the therapy of menopausal disorders by estrogen containing substances there are diseases, for which its systemic administration is restricted. The supplement of the local therapy with physicotherapeutic influence in tissues allows to reduce the pain syndrome, to reduce the length of the treatment and to obtain the earlier restoration of the vagina mucous membrane.